167k views
0 votes
6

1 point
Label the steps in order to solve the following equation:
-11 - 5z = 6 (5z + 4)
&
1
-11 - 5z = 30z + 24
2
-35 = 352
3
-11 = 352 + 24
4
-1=2

1 Answer

4 votes

Answer:

swap the middle two steps to put them in order

Explanation:

The steps in order would be ...

  1. -11 -5z = 30z +24 . . . . . eliminate parentheses
  2. -11 = 35z +24 . . . . . . . . add 5z
  3. -35 = 35z . . . . . . . . . . . . subtract 24
  4. -1 = z . . . . . . . . . . . . . . . . divide by 2
User Rashim
by
5.8k points